Layer-by-layer self-assembled vanadium dioxide and its temperature-dependent light interference - Hu, Hebing (2022)
Vanadium Dioxide (VO2) has gained wide attention for various applications as it undergoes a crystallographic transition from the monoclinic phase to the tetragonal phase at 68 °C, accompanied by huge transmittance contrast in the near-infrared (NIR) range and negligible change in the visible range. In this paper, we present a unique Layer-by-Layer self-assembled approach to construct a VO2/spacing superstructure with controlled VO2 layers, spacing thicknesses, and repeating times. The simulation indicates that such structures give intriguingly temperature-dependent light interference phenomena, which was demonstrated its potential applications in smart windows and the calculated results suggest this approach outperforms existing approaches. This simple and versatile solution-based approach opens a new avenue to fabricate the controlled optical stack which could be explored in other applications.